Theoretical Study of the Stereo-Dynamics of the Reaction $H+CH→H_2+C(^1D)$ (Journal of Atomic and Molecular Sciences, 2021)
The vector correlations between products and reagents for the reactions $H+CH→ H_2+C(^1D)$ at different collision energy have been studied by using the quasi-classical trajectories (QCT) on an ab initio potential energy surface of $1A'$ symmetry. Four polarization-dependent generalized differential cross-sections (PDDCSs) have been calculated in center-of-mass (CM) frame. The distribution $P(θ_r)$ of the angle between $k$ and $j',$ the distribution $P(φ_r)$ of dihedral angle denoting $k-k'-j'$ correlation in the form of polar plots are calculated as well. The effect of deep well in potential surface and differ collision energies on the alignment and the orientation of product molecule $H_2$ rotational angular momentum vectors $j'$ is revealed.
Keywords: quasi-classical trajectories; vectors correlations; stereodynamics.